2008
DOI: 10.1016/j.biomaterials.2008.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Retention of in vitro and in vivo BMP-2 bioactivities in sustained delivery vehicles for bone tissue engineering

Abstract: In this study, we investigated the in vitro and in vivo biologic activity of bone morphogenetic protein 2 (BMP-2) released from four sustained delivery vehicles for bone regeneration. BMP-2 was incorporated in 1) a gelatin hydrogel, 2) poly(lactic-co-glycolic acid) (PLGA) microspheres embedded in a gelatin hydrogel, 3) microspheres embedded in a poly(propylene fumarate) (PPF) scaffold and 4) microspheres embedded in a PPF scaffold surrounded by a gelatin hydrogel. A fraction of the incorporated BMP-2 was radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
245
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(257 citation statements)
references
References 43 publications
10
245
2
Order By: Relevance
“…There were, however, no differences among the three groups at the end of implantation. We speculate prolonged retention of rhBMP-2 in a carrier might result in the loss of its osteoinductive capacity [8]. The release of more growth factors during the early period is apparently important for a carrier, and this is also important for healing of osteoporotic bone defects because osteoporosis most influences the early period of defect healing [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were, however, no differences among the three groups at the end of implantation. We speculate prolonged retention of rhBMP-2 in a carrier might result in the loss of its osteoinductive capacity [8]. The release of more growth factors during the early period is apparently important for a carrier, and this is also important for healing of osteoporotic bone defects because osteoporosis most influences the early period of defect healing [21].…”
Section: Discussionmentioning
confidence: 99%
“…rhBMP-2 is widely used to enhance osteoinduction of bone substitutes [8,11,17,25,28,29]. In several studies rhBMP-2/carrier formulations were associated with bridging of critical-sized bone defects [11,28,29], but rhBMP-2/CPC was the only combination to restore torsional mechanical properties equivalent to those of normal bone [29].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one group recently demonstrated that growth factor-loaded PLGA microspheres imbedded within a poly(propylene fumarate) (PPF) matrix displayed prolonged release of active growth factor in vivo for a period of 12 weeks. 278 This resulted in a substantially better bone formation compared with controls. Other groups have investigated similar approached by entrapping growth factors within PLGA scaffolds which have been mineralized through soaking in a simulated body fluid.…”
Section: Common Copolymers In Bone Engineeringmentioning
confidence: 97%
“…28 Briefly, 20 mL of alkaline working buffer solution, 80 mL of the lysate solution, and 100 mL of substrate solution (5 mM p-nitrophenyl phosphate) were added to a 96-well plate. The plate was incubated at 378C for 1 h, and the reaction was stopped by adding 100 mL of 0.3 N NaOH solution to each well.…”
Section: Alp Activity and Total Proteinmentioning
confidence: 99%
“…These cells are known to respond well to BMP-2 by sensitive changes in alkaline phosphatase production, 28,30 one of the early bone markers, whereas MSCs in the presence of osteogenic molecules may not produce significant amount of ALP when compared with the control (tissue culture plates). 8 The cells were plated at a density of 20,000 cells=cm 2 on 24-well tissue culture plates (Corning, Cambridge, MA).…”
Section: Bmp-2 Release Profiles and Cell Culture In The Presence Of Rmentioning
confidence: 99%